2023
DOI: 10.1001/jamanetworkopen.2023.44295
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Rapid Antigen Tests With Self-Collected vs Health Care Worker–Collected Nasal and Throat Swab Specimens

Tobias Todsen,
Kathrine K. Jakobsen,
Mathias Peter Grønlund
et al.

Abstract: ImportanceSelf- or health care worker (HCW)–collected nasal swab specimens are the preferred sampling method to perform rapid antigen testing for COVID-19, but it is debated whether throat specimens can improve test sensitivity.ObjectiveTo compare the diagnostic accuracy of self- and HCW-collected nasal vs throat swab specimens for COVID-19 rapid antigen testing.Design, Setting, and ParticipantsThis per-protocol multicenter randomized clinical trial was conducted from February 15 through March 25, 2022. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(49 reference statements)
0
0
2
Order By: Relevance
“…Furthermore, self-collected nasal swabs for SARS-CoV-2 are easy to perform, and are highly accepted [ 8 , 24 , 25 ]. Interestingly, the sensitivity of the nasal swabs was slightly higher in the present study compared to previously published studies, stating a sensitivity of approximately 85% for professionally collected or self-collected nasal swabs [ 4 , 26 , 27 , 28 ]. This observed difference may be related to the sensitive quantitative testing method used in the present study compared to semi-quantitative techniques or rapid antigen testing used in previous studies [ 4 , 27 , 29 , 30 ].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, self-collected nasal swabs for SARS-CoV-2 are easy to perform, and are highly accepted [ 8 , 24 , 25 ]. Interestingly, the sensitivity of the nasal swabs was slightly higher in the present study compared to previously published studies, stating a sensitivity of approximately 85% for professionally collected or self-collected nasal swabs [ 4 , 26 , 27 , 28 ]. This observed difference may be related to the sensitive quantitative testing method used in the present study compared to semi-quantitative techniques or rapid antigen testing used in previous studies [ 4 , 27 , 29 , 30 ].…”
Section: Discussioncontrasting
confidence: 78%
“…Interestingly, the sensitivity of the nasal swabs was slightly higher in the present study compared to previously published studies, stating a sensitivity of approximately 85% for professionally collected or self-collected nasal swabs [ 4 , 26 , 27 , 28 ]. This observed difference may be related to the sensitive quantitative testing method used in the present study compared to semi-quantitative techniques or rapid antigen testing used in previous studies [ 4 , 27 , 29 , 30 ]. Although it has been shown that semi-quantitative techniques correlate qualitatively and quantitatively, the sensitivity of the QNAT used in the present study might be slightly higher [ 17 ].…”
Section: Discussioncontrasting
confidence: 78%
“…Some studies perform a throat swab by only collecting specimens from the posterior oropharyngeal wall [ 12 , 13 ], while others also include a swab of the palatine tonsils for SARS-CoV-2 testing [ 14 , 15 ]. However, recent studies suggest that throat swabs, including the palatine tonsils, have a higher sensitivity for SARS-CoV-2 detection than nasal and nasopharyngeal swabs in asymptomatic and early infectious stages [ 16 , 17 ]. SARS-CoV-2 primarily uses the tissue-specific proteases TMPRSS2, TMPRSS4, and TMPRSS11D as cellular entry factors via angiotensin-converting enzyme 2 channels, which are richly expressed in the tonsil crypts [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%